Stress Distribution in a Piezoceramic Disc Applied in Vibration Control of High-Rise Building - Das, A.; Santra, K.C. (Engineering Transactions, 1996)
The shear strain rate measurement is needed to implement active control on a high-rise building for suppressing its vibration. A piezoceramic disc can be used to measure the shear strain. Shearing stress distribution and displacements in such a disc sensor have been investigated. This study is aimed at proper selection of the type of material for construction of the disc.